140 Redefining gut Barrier Function for Beef and Dairy Cattle. (21st September 2022) - Penner, Gregory B
Abstract: Of the many roles that the gastrointestinal tract (GIT) must facilitate, coordinated regulation of molecule movement across the gastrointestinal is key. This coordinated regulation allows for nutrient absorption while limiting permeation of non-desired molecules and is referred to as barrier function. Barrier function of the GIT includes intrinsic, extrinsic, and immunological factors, but generally permeability assessments are conducted to evaluate the whole-animal response and most studies focus on the extrinsic components of GIT barrier function. Common approaches to evaluate GIT permeability include the use of inert external markers varying in size and their measurement in blood or urine. Methodology exists for ex vivo, in vitro, and in vivo assessment; however, only in ex vivo and in vitro methods currently allow regionally specific information. Moreover, ex vivo studies have been essential to further elucidate factors that affect permeability such as osmolality, pH, and bioactive components such as histamine and lipopolysaccharides. For ruminants, extensive microbial degradation challenges the use of fermentable substrates as markers when assessing permeability and there is interest to compartmentalize permeability by region of the GIT. Recent research using dual markers to allow for total GIT and post-ruminal permeability have highlighted that regional permeability responses may be affected by production system, environmental conditions, and dietary characteristics. Future research is needed to improve the understanding of factors that affect GIT permeability, the regions involved, and strategies to support regulation of permeability.